1993
DOI: 10.1002/1097-0142(19930315)71:6<1938::aid-cncr2820710603>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Progression of signet ring cell carcinomas in the human stomach

Abstract: Background. Stomach cancers show various growth patterns. It remains to be clarified how this variability is related to the genetic changes that occur during tumor progression. Methods. To estimate the genetic changes from tumor ploidy, maps were made (using DNA cytofluorometry of metaphase cells in histologic sections) of 39 advanced signet ring cell carcinomas of the human stomach and correlated with tumor stage and the size of the primary mucosal lesion. Results. Aneuploid area and multipattern aneuploidy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Another merit of static cytofluorometry is an ability to detect small polyploid populations that cannot be detected by the usual flow-cytometric analysis. It is important to distinguish DNA diploidy with polyploidy from that without polyploidy because the presence of polyploidy is also considered to reflect chromosomal instability, possibly reflecting near-diploid aneuploidy at the chromosome level [29].…”
Section: Discussionsupporting
confidence: 92%
“…Another merit of static cytofluorometry is an ability to detect small polyploid populations that cannot be detected by the usual flow-cytometric analysis. It is important to distinguish DNA diploidy with polyploidy from that without polyploidy because the presence of polyploidy is also considered to reflect chromosomal instability, possibly reflecting near-diploid aneuploidy at the chromosome level [29].…”
Section: Discussionsupporting
confidence: 92%
“…One candidate we have examined is the DNA-ploidy pattern, because it seemed very important to examine quantitative change of DNA to study a mechanism of oncogene amplification at an earlier stage. In addition, the occurrence of both DNA-aneuploidy and DNA-polyploidy has been reported by us to correlate with the progression of gastric cancer [12,13,28]. The Table 2 DNA ploidy pattern (with polyploidy) of gastric cancers studied& / t b l .…”
Section: Discussionmentioning
confidence: 89%
“…We consider that it is important to detect polyploidy to know about chromosome instability in the tumour, because polyploidy is detected quite commonly in DNA-aneuploid tumours but not in the normal gastric mucosa [12,28]. Furthermore, there is experimental and clinical evidence that polyploidization precedes the occurrence of DNA-aneuploidy and further evolution of new stemlines from the DNA-aneuploid cell population during tumour progression [6,9,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…The mapping of DNA ploidy in individual tumors demonstrated that intramucosal spreading growth is characteristic of DNA-diploid tumor cells of this type and that the appearance of a DNA-aneuploid subclone is closely related to enhanced chromosomal instability and deeply invasive growth [23]. Such subclones are reported to occur in a stochastic rather than a time-dependent manner [24]. It may be because the occurrence of a subclone with an enhanced growth advantage is a much rarer event than the occurrence of a neutral subclone with changes in mucin phenotype.…”
Section: Discussionmentioning
confidence: 99%